The 21st Century Model for Pedagogical Transformation: Exploring Teachers' Identity and Professional Responsibility - Gyawali, Yadu Prasad; Mehndroo, Meghna (Journal of NELTA Gandaki, 2023)
This study proposes to facilitate the implementation of learner-centred, language-integrated, and future-oriented teaching and learning methodologies, per the National Education Policy (NEP 2020) principles and global educational perspectives. The primary goal of the study is to bridge the gap between traditional pedagogical approaches and modern educational requirements. The independent discussion with four educational experts from Nepal and content analysis were regarded as the methods of the study. The paper highlights the importance of learner-focused teaching and learning strategies, where learners are encouraged to develop creativity and critical awareness. Furthermore, Sustainable Development Goal 4, India's NEP 2020, and Nepal's education policy aim to improve educational quality and accessibility, focusing on fair access and inclusion for those in need. India and Nepal also prioritize teacher training and development to improve education systems, contributing to Sustainable Development Goal 4. The Article concludes by focusing on language, logic, and social context, in line with recent reports and research studies, to ensure outcome-based learning in a changing world. Similarly, some suggestive parameters for curricula reform to enhance sustainable development goals in line with the 21st-century mindset have been discussed.